CORRELATION OF SETTLEMENT QUALITY WITH COMMUNITY QUALITY OF LIFE USING GIS (Case Study: Puger District, Jember Regency) - Nurina Awanis; Sri Sukmawati; Rindang Alfiah (UNEJ e-Proceeding, 2022)
Puger District is one of the sub-districts that has a lot of natural resources such as mining. Lime mining activities in Gunung Sadeng certainly affect the quality of the housing environment and also the standard of living of residents in Puger District. The level of the residential environment is the quality of environmental competence to fulfill the needs of the place where it lives. The quality of this settlement includes the healthy condition of the environment as well as housing as well as environmental infrastructure, air quality, as well as residential areas. Especially in the existing conditions of dense settlement density conditions, solid waste conditions and poor road conditions as well as air quality that affects public health, so this study aims to search for knowledge about the state of quality of life as well as the quality of settlements in Puger District and the relationship between the two. In finding the quality of settlements, it is done by interpreting sas images using GIS and quality of life using Ms. Excel. The analytical method used is correlation analysis in order to determine the relationship between the quality of life and the quality of settlements. From the results of the study, it was found that Puger District had moderate quality of life as well as moderate quality of settlements and from correlation analysis, it was found that quality of life and quality of settlements had a moderate correlation coefficient with a positive value, meaning that the relationship between two variables was directly proportional. Keywords: Settlement quality, Community Of Life